PERAN MEDIATOR DAN BP4 MENGATASI PERSOALAN - Yandi, Rus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This paper will elaborate on the issue of divorce in the homeland that needs serious attention from the special elements of the nation and society in general, as well as the solution. Divorce is increasingly increasing, because it cannot be underestimated, because it causes the low existence of the nation's life. The dilemma The case continues to soar, even though the ideals and hopes of all couples who will get married never have the intention to finally separate. However, in reality, these hopes are dashed as storms and waves hit the household plume, many trials end in bitter decisions not to end. together again. There are a number of things that should be considered in highlighting this issue, first the role of mediation, BP4 as well as regulations that apply so that the business is expected to overcome divorce between married couples. Therefore, the focus of this writing is even though the role and function of mediation in reconciling the parties. So that in the future the results can be more effective and efficient in overcoming the problem and getting a positive contribution to the life of the community, the state and the nation to support household harmony.